Learning Styles and the Use of Multiple Representations in Basic Electronic Lectures for Physics Education Students: A Critical Study - Febrian Virijai; Nuryani Rustaman; Asep Kadarohman; Dadi Rusdiana; Eka Cahya Prima; Hazrati Ashel; Ridwan Ridwan (Pendidikan Fisika Universitas Nurul Huda, 2024)
Physics education graduates will produce quality teacher candidates. However, physics education students have difficulty understanding basic electronics lectures. Multiple representation-based lectures are needed to improve students' cognitive understanding and skills. This representative multiple is adapted to student learning styles. The problem comes from the lack of references that explain the learning styles of prospective physics teacher students with multiple representative integrated basic electronics lectures. The problem formulation that arises is how students' learning styles are presented and how basic electronics lectures are represented. The method used is mixed methods with a data triangulation design. Quantitative data comes from questionnaires of 50 students and qualitative data comes from interviews with lecturers teaching basic electronics courses. This research was conducted at a university in West Sumatra. The research results show that student understanding is still low and research needs to be carried out regarding the development of basic electronics programs based on multiple representations to improve students' cognitive understanding